Properties of the White Sea littoral sediments and their influence on the fauna and distribution of Harpacticoida. - Rybnikov, P V; Kondar', D V; Azovskii, A I (PANGAEA, 2003)
Dependence of the faunal composition and species structure of the White Sea littoral Harpacticoida on sediment properties was studied. Three groups of species could be distinguished according to their relationship with sediment properties: (1) species typical of silty sediments, (2) species preferring sediments with high gravel content, and (3) species inhabiting well-sorted washed sands. Vertical distribution of crustaceans within sediments of different types was studied. Vertical migrations of harpacticoids (3) during the tidal cycle were described. Data on interannual variability of harpacticoid fauna are presented.
(Table 2) Fauna Harpacticoida and its distribution in the Kandalaksha Bay (White Sea) in July 1998 and 1999
Keywords: Archive of Ocean Data; ARCOD; BC; Benthic biomass, wet weight; Biomass, wet mass per area; Box corer; ChR1-98; ChR2-98; ChR3-98; DEPTH, sediment/rock; Kandalaksha Bay, White Sea; Number of species; Olen1-98; Olen1-99; Olen2-98; Olen2-99; Olen3-98; Olen3-99; Penetration depth; Sediment type; Species; WSBS1-99; WSBS2-99; WSBS3-99